Revitalizing the Role of the Mosque in Local Potential-Based Community Economic Empowerment - Fathor Rozi (GUYUB: Journal of Community Engagement, 2025)
This study aims to identify and develop the community’s economic potential around the mosque in Suboh District, Situbondo, based on local excellence. The method used in this study is the Asset-Based Community Development (ABCD) approach, which focuses on utilizing local resources through entrepreneurship training and local product processing. This study uses a qualitative method with data collection techniques through interviews, observations, and documentation. The study results indicate that the community has basic skills in processing local agricultural and craft products but faces marketing, packaging, and business management obstacles. The entrepreneurship training improved the community’s skills and confidence in developing products based on local potential. However, challenges related to business sustainability and business management still exist. The implications of this study are the importance of ongoing mentoring programs and business management training to ensure long-term success. This study contributes to the development of the local economy and community empowerment based on local resources and is a reference for community empowerment programs in other areas